2015
DOI: 10.3832/ifor0982-007
|View full text |Cite
|
Sign up to set email alerts
|

Day and night respiration of three tree species in a temperate forest of northeastern China

Abstract: © iForest -Biogeosciences and Forestry IntroductionDark respiration (non-photorespiratory respiration), which occurs both in light and in darkness, has a critical function in modulating the carbon balance of plants and terrestrial ecosystems. Ryan (1991) showed that the proportion of carbon consumption by respiration is nearly 70% of the total photosynthetic carbon fixation, and leaf respiration accounts for approximately 50% of total plant respiration (Poorter et al. 1991). At the ecosystem level, CO2 emissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…In theory, three CO 2 response curves obtained by varying CO 2 concentrations from 150 to 40 µmol CO 2 mol −1 under three PPFDs (150, 100 and 50 µmol m −2 s −1 ) would intersect with each other at a point, and the intersection point at x-axis and y-axis were considered to Г * and R d , respectively. But in practice, these three linear regressions of the intersected A n -C i curves formed a triangle range rather than a single point 40 (Fig. S1), and the Г * and R d were calculated as the barycenter of the triangle formed by the intersection of the three lines at x-axis and y-axis, respectively, according to our previous published method 40 .…”
Section: Plant Materials and Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…In theory, three CO 2 response curves obtained by varying CO 2 concentrations from 150 to 40 µmol CO 2 mol −1 under three PPFDs (150, 100 and 50 µmol m −2 s −1 ) would intersect with each other at a point, and the intersection point at x-axis and y-axis were considered to Г * and R d , respectively. But in practice, these three linear regressions of the intersected A n -C i curves formed a triangle range rather than a single point 40 (Fig. S1), and the Г * and R d were calculated as the barycenter of the triangle formed by the intersection of the three lines at x-axis and y-axis, respectively, according to our previous published method 40 .…”
Section: Plant Materials and Experimental Designmentioning
confidence: 99%
“…But in practice, these three linear regressions of the intersected A n -C i curves formed a triangle range rather than a single point 40 (Fig. S1), and the Г * and R d were calculated as the barycenter of the triangle formed by the intersection of the three lines at x-axis and y-axis, respectively, according to our previous published method 40 . The values of Г * and R d during soil nitrogen additions were shown in Table S2.…”
Section: Plant Materials and Experimental Designmentioning
confidence: 99%
“…To partition NEE fluxes into the originating R eco and GEE fluxes, night time NEE data are generally used to extrapolate R eco during the day by adopting a temperature response function [50], although it has been suggested that this method may lead to an overestimation of R eco [61]. Alternatively, the light response curve estimated during daytime is used, and the respiration is obtained from the intercept on the ordinate [62].…”
Section: Discussionmentioning
confidence: 99%
“…However, light can inhibit plant respiration (Parnik et al 2010;Ayub et al 2014). For example, Sun et al (2015) found that daily respiration decreased with increasing photosynthetic photon flux density, and a small amount of light can also inhibit respiration. However, Wang and Mao (2007) suggested that light was not the main factor affecting respiration.…”
Section: Environmental Factors Influencing Variations In Ementioning
confidence: 99%